A modified aluminum alloy composite foil and its preparation process

CN119752276APending Publication Date: 2025-04-04JIANGSU ALCHA ALUMINUM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411819805.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

[0007]针对现有技术的不足,本发明提供了一种改性铝合金复合箔及其制备工艺,由于采用了纳米S i O2,阻碍了腐蚀介质的渗入,延长了腐蚀介质到达换热器内部的时间,所以,有效解决了现有的换热器用铝合金复合箔在使用时,耐腐蚀能力差的技术问题,进而提高了复合涂层的防腐性能,且添加纳米颗粒的复合涂层硬度增高,此外,在3.5%NaC l溶液腐蚀下的时间有传统的100d提高到了160d,可见添加通过采用S iO2纳米复合涂层可有效地延长换热器耐腐蚀寿命,解决现有的换热器用铝合金复合箔在使用时,耐腐蚀能力差的技术问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752276A_ABST
    Figure CN119752276A_ABST
Patent Text Reader

Abstract

The invention discloses a modified aluminum alloy composite foil and a preparation process thereof, and relates to the technical field of aluminum foil. The alloy powder is made of the following percentage raw materials: 17-29% zinc, 0.02-0.07% lanthanum, 0-0.05% copper, 0.02-0.09% iron, and the balance is aluminum. The modified aluminum alloy composite foil and the preparation process thereof described in the invention, due to the use of nano SiO2, hinder the penetration of corrosive media and prolong the time for the corrosive media to reach the inside of the heat exchanger, so the technical problem of poor corrosion resistance of the existing aluminum alloy composite foil for heat exchangers during use is effectively solved, thereby improving the anti-corrosion performance of the composite coating, and the hardness of the composite coating with the addition of nanoparticles is increased. In addition, the time under 3.5% NaCl solution corrosion is increased from the traditional 100d to 160d, which shows that the addition of the SiO2 nano composite coating can effectively prolong the corrosion resistance life of the heat exchanger.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum foil, and in particular to a modified aluminum alloy composite foil and a preparation process thereof. Background Art

[0002] The heat exchanger of the air conditioner carries the function of heat exchange of the air conditioner. The heat exchanger used in general household air conditioners is a steel tube aluminum fin heat exchanger. The main thermal resistance of the heat exchanger is the heat exchange resistance between the air-side fins and the air, which accounts for about 70-80% of the total thermal resistance of the heat exchanger. The condition of the aluminum fins directly affects the heat exchange efficiency of the heat exchanger, thereby affecting whether the air conditioner is energy-saving.

[0003] At present, a Chinese patent with the existing patent application number "CN202310866821.2" discloses a graphene composite aluminum foil, which belongs to the field of aluminum foil technology. The preparation steps are as follows: the first step is to prepare the following raw materials by weight: 40-50 parts of monofunctional UV curable oligomer, 60-80 parts of waterborne polyurethane acrylate oligomer, 5-10 parts of organic modified graphene, 3-5 parts of thermal conductive fiber, 1-3 parts of photoinitiator, and 1-5 parts of emulsifier; the second step is to mix the raw materials in the first step, and add water to dilute and prepare a mass A coating with a fraction of 1% is applied to the surface of a substrate with a coating thickness of 10-15 μm, and the coating is cured by ultraviolet irradiation at a temperature of 80-120° C. and a wavelength of 250-400 nm for 3-5 minutes to obtain a graphene composite aluminum foil. The graphene composite aluminum foil prepared by the present invention not only has good thermal conductivity, but also has oil resistance and solvent resistance. Although it can have good electrical conductivity, its corrosion resistance is seriously insufficient. The most common temperature of an air conditioner heat exchanger is rust. Therefore, it is necessary to have good electrical conductivity and corrosion resistance at the same time.

[0004] However, during the implementation of the above technical solution, it was found that there were at least the following technical problems:

[0005] Poor corrosion resistance: When the existing aluminum alloy composite foil for heat exchangers is used, it needs to continue heat exchange treatment and is mostly installed outdoors. Therefore, the fins on the surface of the heat exchanger are very easy to come into contact with water. The corrosion is caused by the dissolution of carbon dioxide in the air into water, and the water forms an acidic electrolyte, which accelerates the corrosion of the material. Therefore, the most common problem is the corrosion and rust of the fins. In addition, the problems caused by corrosion are not only the mottled marks on the surface of the heat exchanger, but also the reduced heat exchange effect, the shortened service life caused by the corrosion of the material, and the deterioration of the heat exchange medium on the inner wall of the heat exchanger. This is because after the material corrodes, a layer of fluffy oxide is covered on the surface of the material, which makes it impossible for heat to pass through effectively. The deterioration of the heat exchange medium mostly occurs in the later stage of corrosion. With the continuous corrosion of the fins, it gradually moves to the center of the heat exchanger, causing the heat exchange medium inside the heat exchanger to deteriorate. For this reason, we propose a modified aluminum alloy composite foil and its preparation process. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In view of the deficiencies in the prior art, the present invention provides a modified aluminum alloy composite foil and a preparation process thereof. Due to the use of nano SiO2, the penetration of corrosive media is hindered and the time for the corrosive media to reach the inside of the heat exchanger is prolonged. Therefore, the technical problem that the existing aluminum alloy composite foil for heat exchangers has poor corrosion resistance when in use is effectively solved, thereby improving the anti-corrosion performance of the composite coating, and the hardness of the composite coating with the addition of nanoparticles is increased. In addition, the time for corrosion under 3.5% NaCl solution is increased from the traditional 100d to 160d. It can be seen that the addition of the SiO2 nano-composite coating can effectively prolong the corrosion resistance life of the heat exchanger, and solve the technical problem that the existing aluminum alloy composite foil for heat exchangers has poor corrosion resistance when in use.

[0008] (II) Technical solution

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] A modified aluminum alloy composite foil, which is prepared by compounding alloy powder and modified composite material;

[0011] The alloy powder is made of the following percentage raw materials: 17-29% zinc, 0.02-0.07% lanthanum, 0-0.05% copper, 0.02-0.09% iron, and the balance is aluminum;

[0012] The modified composite material is made of the following percentage raw materials: 0.22-0.35% of silicon dioxide, 8-9% of Zn-Al alloy powder, 22-28% of PU / EP polymer, 26-30% of D-230 curing agent, 23-25% of silane coupling agent KH-550, 5-7% of OP-10 emulsifier, 2-3% of 1,4-propylene glycol, 8-10% of ethyl acetate / xylene, and the balance is distilled water;

[0013] The preparation process of the modified composite material is as follows:

[0014] S1. Mix polyurethane and epoxy resin in a ratio of 1:32-38 and stir at high speed for 1 hour. Sampling and testing until the free isocyanate group (-NCO) content in the sample is less than 0.1%. Then, slowly add the uniform mixture of propylene glycol butyl ether and silane coupling agent KH-550 in a ratio of 1:11-13 and stir for 15 minutes into the mixed resin of polyurethane / epoxy resin and stir at high speed for 1 hour.

[0015] S2, adding nano-SiO2 to the mixed solution obtained in step S1, stirring at high speed for 30 minutes, slowly adding weighed Zn-Al alloy powder, then adding emulsifier OP-10 and defoamer and stirring at high speed until the slurry is completely dispersed, to obtain mixed base liquid A;

[0016] S3, take appropriate amount of curing agent polyetheramine D-230 and accelerator DMP-30 and stir them thoroughly, then weigh ethyl acetate / xylene solvent in a certain proportion to the resin and mix them and continue stirring to obtain mixed base liquid B;

[0017] S4. Mix the above-mentioned mixed base liquids A and B, and stir them at high speed using a magnetic stirrer for 3 hours to obtain a modified composite coating.

[0018] In some examples, in step S1, the raw materials of polyurethane and epoxy resin need to be dehydrated before use;

[0019] Dehydration treatment: Place the raw materials in a vacuum drying oven, evacuate the air, heat at 110-120℃ for 2-3h, and after drying, cool to 50℃ and keep warm for later use.

[0020] In some examples, in step S1, a mixture of propylene glycol butyl ether and silane coupling agent KH-550 is added to a mixed resin of polyurethane / epoxy resin by step-by-step mixing, and propylene glycol butyl ether and silane coupling agent KH-550 are evenly divided into 10 parts;

[0021] Preliminary mixing: Take 6 parts of propylene glycol butyl ether and silane coupling agent KH-550, mix them, stir at a stirring speed of 12-15r / min, and stir for 6-8min;

[0022] Constant temperature: slowly add the mixture of propylene glycol butyl ether and silane coupling agent KH-550 into the mixed resin of polyurethane / epoxy resin, control the temperature within 35-38℃, and stir slowly;

[0023] Heating: Raise the temperature to 45°C and maintain for 30-35 minutes. During the maintenance period, add propylene glycol butyl ether to the mixed resin in the form of drops, and add 10-12 drops each time, and let it stand for 10 minutes until all the propylene glycol butyl ether is added. Similarly, use this method to add the silane coupling agent KH-550 to the mixed resin.

[0024] In some examples, during the dropwise addition and mixing, the temperature of propylene glycol butyl ether and silane coupling agent KH-550 during the dropwise addition is consistent with the temperature after the temperature increase.

[0025] In some examples, the aluminum alloy in the alloy powder is spherical aluminum, and the spherical aluminum is dispersed in anhydrous ethanol, and then triethanolamine is added, and the mixture is heated, stirred, washed, and dried to obtain hydroxylated spherical aluminum;

[0026] Wherein, the weight ratio of spherical aluminum powder, anhydrous ethanol and triethanolamine is 62-80:21-35:1-2.

[0027] In some examples, the diameter of the spherical aluminum is 6-8 μm.

[0028] In some examples, nano-SiO2 undergoes a hydrolysis reaction under a specific environment and eventually transforms into a gel, and then the solvent is evaporated by heating or other methods to become an oxide gel with a grid structure, wherein the precursor is a metal salt or an alkoxide metal;

[0029] Among them, the hydroxyl group replaces the alkoxy group (-OC2H5) in ethyl orthosilicate to obtain the product silicic acid; then the various silicic acid monomers undergo dehydration reaction and condensation reaction to obtain nano-SiO2.

[0030] In some examples, when preparing the alloy powder, metal iron, lanthanum, copper, and aluminum are melted and mixed to obtain a comminuted alloy, the comminuted alloy is homogenized at a temperature of 560-580°C for 8 hours to obtain a composite alloy, and the composite alloy is ball-milled to obtain the alloy powder.

[0031] In some examples, a process for preparing a modified aluminum alloy composite foil includes the following steps:

[0032] The alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are mixed, and the slurry is coated and dried to obtain an aluminum alloy composite foil;

[0033] The mass ratio of the alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane is 7:1-3:1.

[0034] In some examples, after the aluminum alloy composite foil is solidified, an electromagnetic heating roller is used to roll the surface of the aluminum alloy composite foil at a pressure of 2.1-2.5 MPa and a heating temperature of 660-670° C. The rolling is repeated 2-3 times;

[0035] Each time the rolling process is performed, a layer of spherical aluminum particles is applied to the surface of the aluminum alloy composite foil.

[0036] (III) Beneficial effects

[0037] 1. The use of nano-SiO2 hinders the penetration of corrosive media and prolongs the time for corrosive media to reach the inside of the heat exchanger. Therefore, the technical problem of poor corrosion resistance of the existing aluminum alloy composite foil for heat exchangers during use is effectively solved, thereby improving the anti-corrosion performance of the composite coating, and the hardness of the composite coating with the addition of nanoparticles is increased. In addition, the time under 3.5% NaCl solution corrosion is increased from the traditional 100d to 160d. It can be seen that the addition of SiO2 nano-composite coating can effectively prolong the corrosion resistance life of the heat exchanger.

[0038] 2. The mixture of propylene glycol butyl ether and silane coupling agent KH-550 is added to the mixed resin of polyurethane / epoxy resin by a distributed mixing method, thereby reducing the risk caused by the reaction of raw materials while ensuring the full reaction between the raw materials.

[0039] 3. The modified aluminum alloy composite foil provided in the present application has the ability to cope with harsh environments such as high temperature, acid, and alkali, and can ensure that even if it is exposed to the outdoor environment for a long time, it can maintain good performance and meet the use requirements of the heat exchanger. Moreover, compared with the traditional graphene composite aluminum foil, the modified aluminum alloy composite foil prepared by the present invention has a higher effect in corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.

[0041] Figure 1 The figure is a structural diagram of the preparation method of the modified composite material of the present invention. DETAILED DESCRIPTION

[0042] The embodiment of the present application solves the technical problem of poor corrosion resistance of aluminum alloy composite foil for heat exchangers in the prior art by providing a modified aluminum alloy composite foil and a preparation process thereof. When the existing aluminum alloy composite foil for heat exchangers is in use, the use of nano SiO2 hinders the penetration of corrosive media and prolongs the time for the corrosive media to reach the inside of the heat exchanger, thereby improving the anti-corrosion performance of the composite coating, and the hardness of the composite coating with the addition of nanoparticles is increased. In addition, the time under corrosion with 3.5% NaCl solution is increased from the traditional 100d to 160d. It can be seen that the addition of SiO2 nano-composite coating can effectively prolong the corrosion resistance life of the heat exchanger.

[0043] The technical solution in the embodiment of the present application is to solve the technical problem that the aluminum alloy composite foil for heat exchanger in the prior art has poor corrosion resistance when in use. The overall idea is as follows:

[0044] Embodiment 1: In view of the problems existing in the prior art, the present invention provides a modified aluminum alloy composite foil, which is prepared by compounding alloy powder and modified composite material;

[0045] The alloy powder is made of the following percentages of raw materials: 23% zinc, 0.05% lanthanum, 0.05% copper, 0.07% iron, and the balance is aluminum. When preparing the alloy powder, the metal iron, lanthanum, copper, and aluminum are melted and blended to obtain a commingled alloy. The commingled alloy is homogenized at a temperature of 570° C. for 8 hours to obtain a composite alloy. The composite alloy is ball-milled to obtain the alloy powder.

[0046] The preparation process of the modified aluminum alloy composite foil comprises the following steps:

[0047] The alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are mixed, and the slurry is coated and dried to obtain an aluminum alloy composite foil;

[0048] The alloy powder, the modified composite material, and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are used in a mass ratio of 7:1:1. After the aluminum alloy composite foil solidifies, an electromagnetic heating roller is used to roll the surface of the aluminum alloy composite foil at a pressure of 2.2 MPa and a heating temperature of 665°C. The rolling is repeated three times, and each time a layer of spherical aluminum particles is applied to the surface of the aluminum alloy composite foil.

[0049] The modified composite material is made of the following raw materials in percentage: 0.32% of silicon dioxide, 8% of Zn-Al alloy powder, 23% of PU / EP polymer, 26% of D-230 curing agent, 23% of silane coupling agent KH-550, 5% of OP-10 emulsifier, 2% of 1,4-propylene glycol, 8% of ethyl acetate / xylene, and the balance is distilled water.

[0050] Nano-SiO2 undergoes a hydrolysis reaction under a specific environment and eventually turns into a gel, and then the solvent is evaporated by heating or other methods to become an oxide gel with a grid structure, wherein the precursor is a metal salt or an alkoxide metal;

[0051] Among them, the hydroxyl group replaces the alkoxy group (-OC2H5) in ethyl orthosilicate to obtain the product silicic acid; then the various silicic acid monomers undergo dehydration reaction and condensation reaction to obtain nano-SiO2.

[0052] The preparation process of the modified composite material is as follows:

[0053] S1. Mix polyurethane and epoxy resin in a ratio of 1:32 and stir at high speed for 1 hour. Sampling and testing until the free isocyanate group (-NCO) content in the sample is less than 0.1%. Then, a uniform mixture of propylene glycol butyl ether and silane coupling agent KH-550 in a ratio of 1:12 and stirred for 15 minutes is slowly added to the mixed resin of polyurethane / epoxy resin and stirred at high speed for 1 hour. The raw materials of polyurethane and epoxy resin need to be dehydrated before use. Dehydration treatment: put the raw materials into a vacuum drying oven, evacuate, heat at 110°C for 2 hours, cool to 50°C after drying and keep warm for use;

[0054] The mixture of propylene glycol butyl ether and silane coupling agent KH-550 is added to the mixed resin of polyurethane / epoxy resin by step-by-step mixing, and the propylene glycol butyl ether and silane coupling agent KH-550 are evenly divided into 10 parts;

[0055] Preliminary mixing: Take 6 parts of propylene glycol butyl ether and silane coupling agent KH-550, mix them, stir at a stirring speed of 12r / min, and stir for 7min;

[0056] Constant temperature: slowly add the mixture of propylene glycol butyl ether and silane coupling agent KH-550 into the mixed resin of polyurethane / epoxy resin, control the temperature within 35°C, and stir slowly;

[0057] Heating: raising the temperature to 45°C and maintaining it for 32 minutes, and in the maintaining stage, adding propylene glycol butyl ether to the mixed resin in the form of drops, and each time 10 drops are added, standing for 10 minutes, until all the propylene glycol butyl ether is added; similarly, the silane coupling agent KH-550 is added to the mixed resin by this method, and during the dropwise addition and mixing, the temperature of propylene glycol butyl ether and silane coupling agent KH-550 when dropping is consistent with the temperature after heating, the aluminum alloy in the alloy powder is spherical aluminum, and the spherical aluminum is dispersed in anhydrous ethanol, and then triethanolamine is added, and the hydroxylated spherical aluminum is obtained by heating, stirring, washing, and drying;

[0058] The weight ratio of spherical aluminum powder, anhydrous ethanol and triethanolamine is 74:31:2, and the diameter of the spherical aluminum is 7 μm;

[0059] S2, adding nano-SiO2 to the mixed solution obtained in step S1, stirring at high speed for 30 minutes, slowly adding weighed Zn-Al alloy powder, then adding emulsifier OP-10 and defoamer and stirring at high speed until the slurry is completely dispersed, to obtain mixed base liquid A;

[0060] S3, take appropriate amount of curing agent polyetheramine D-230 and accelerator DMP-30 and stir them thoroughly, then weigh ethyl acetate / xylene solvent in a certain proportion to the resin and mix them and continue stirring to obtain mixed base liquid B;

[0061] S4. Mix the above-mentioned mixed base liquids A and B, and stir them at high speed using a magnetic stirrer for 3 hours to obtain a modified composite coating.

[0062] Embodiment 2: In view of the problems existing in the prior art, the present invention provides a modified aluminum alloy composite foil, which is prepared by compounding alloy powder and modified composite material;

[0063] The alloy powder is made of the following percentages of raw materials: 23% zinc, 0.05% lanthanum, 0.05% copper, 0.07% iron, and the balance is aluminum. When preparing the alloy powder, the metal iron, lanthanum, copper, and aluminum are melted and blended to obtain a commingled alloy. The commingled alloy is homogenized at a temperature of 570° C. for 8 hours to obtain a composite alloy. The composite alloy is ball-milled to obtain the alloy powder.

[0064] The preparation process of the modified aluminum alloy composite foil comprises the following steps:

[0065] The alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are mixed, and the slurry is coated and dried to obtain an aluminum alloy composite foil;

[0066] The alloy powder, the modified composite material, and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are used in a mass ratio of 7:2:1. After the aluminum alloy composite foil solidifies, an electromagnetic heating roller is used to roll the surface of the aluminum alloy composite foil at a pressure of 2.2 MPa and a heating temperature of 665°C. The rolling is repeated three times, and each time a layer of spherical aluminum particles is applied to the surface of the aluminum alloy composite foil.

[0067] The modified composite material is made of the following raw materials in percentage: 0.32% of silicon dioxide, 8% of Zn-Al alloy powder, 23% of PU / EP polymer, 26% of D-230 curing agent, 23% of silane coupling agent KH-550, 5% of OP-10 emulsifier, 2% of 1,4-propylene glycol, 8% of ethyl acetate / xylene, and the balance is distilled water.

[0068] Nano-SiO2 undergoes a hydrolysis reaction under a specific environment and eventually turns into a gel, and then the solvent is evaporated by heating or other methods to become an oxide gel with a grid structure, wherein the precursor is a metal salt or an alkoxide metal;

[0069] Among them, the hydroxyl group replaces the alkoxy group (-OC2H5) in ethyl orthosilicate to obtain the product silicic acid; then the various silicic acid monomers undergo dehydration reaction and condensation reaction to obtain nano-SiO2.

[0070] The preparation process of the modified composite material is as follows:

[0071] S1. Mix polyurethane and epoxy resin in a ratio of 1:32 and stir at high speed for 1 hour. Sampling and testing until the free isocyanate group (-NCO) content in the sample is less than 0.1%. Then, a uniform mixture of propylene glycol butyl ether and silane coupling agent KH-550 in a ratio of 1:12 and stirred for 15 minutes is slowly added to the mixed resin of polyurethane / epoxy resin and stirred at high speed for 1 hour. The raw materials of polyurethane and epoxy resin need to be dehydrated before use. Dehydration treatment: put the raw materials into a vacuum drying oven, evacuate, heat at 110°C for 2 hours, cool to 50°C after drying and keep warm for use;

[0072] The mixture of propylene glycol butyl ether and silane coupling agent KH-550 is added to the mixed resin of polyurethane / epoxy resin by step-by-step mixing, and the propylene glycol butyl ether and silane coupling agent KH-550 are evenly divided into 10 parts;

[0073] Preliminary mixing: Take 6 parts of propylene glycol butyl ether and silane coupling agent KH-550, mix them, stir at a stirring speed of 12r / min, and stir for 7min;

[0074] Constant temperature: slowly add the mixture of propylene glycol butyl ether and silane coupling agent KH-550 into the mixed resin of polyurethane / epoxy resin, control the temperature within 35°C, and stir slowly;

[0075] Heating: raising the temperature to 45°C and maintaining it for 32 minutes, and in the maintaining stage, adding propylene glycol butyl ether to the mixed resin in the form of drops, and each time 10 drops are added, standing for 10 minutes, until all the propylene glycol butyl ether is added; similarly, the silane coupling agent KH-550 is added to the mixed resin by this method, and during the dropwise addition and mixing, the temperature of propylene glycol butyl ether and silane coupling agent KH-550 when dropping is consistent with the temperature after heating, the aluminum alloy in the alloy powder is spherical aluminum, and the spherical aluminum is dispersed in anhydrous ethanol, and then triethanolamine is added, and the hydroxylated spherical aluminum is obtained by heating, stirring, washing, and drying;

[0076] The weight ratio of spherical aluminum powder, anhydrous ethanol and triethanolamine is 74:31:2, and the diameter of the spherical aluminum is 7 μm;

[0077] S2, adding nano-SiO2 to the mixed solution obtained in step S1, stirring at high speed for 30 minutes, slowly adding weighed Zn-Al alloy powder, and then adding emulsifier OP-10 and defoamer and stirring at high speed until the slurry is completely dispersed, to obtain a mixed base liquid A;

[0078] S3, take appropriate amount of curing agent polyetheramine D-230 and accelerator DMP-30 and stir them thoroughly, then weigh ethyl acetate / xylene solvent in a certain proportion to the resin and mix them and continue stirring to obtain mixed base liquid B;

[0079] S4. Mix the above-mentioned mixed base liquids A and B, and stir them at high speed using a magnetic stirrer for 3 hours to obtain a modified composite coating.

[0080] Embodiment 3: In view of the problems existing in the prior art, the present invention provides a modified aluminum alloy composite foil, which is prepared by compounding alloy powder and modified composite material;

[0081] The alloy powder is made of the following percentages of raw materials: 23% zinc, 0.05% lanthanum, 0.05% copper, 0.07% iron, and the balance is aluminum. When preparing the alloy powder, the metal iron, lanthanum, copper, and aluminum are melted and blended to obtain a commingled alloy. The commingled alloy is homogenized at a temperature of 570° C. for 8 hours to obtain a composite alloy. The composite alloy is ball-milled to obtain the alloy powder.

[0082] The preparation process of the modified aluminum alloy composite foil comprises the following steps:

[0083] The alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are mixed, and the slurry is coated and dried to obtain an aluminum alloy composite foil;

[0084] The alloy powder, the modified composite material, and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are used in a mass ratio of 7:3:1. After the aluminum alloy composite foil solidifies, an electromagnetic heating roller is used to roll the surface of the aluminum alloy composite foil at a pressure of 2.2 MPa and a heating temperature of 665°C. The rolling is repeated three times, and each time a layer of spherical aluminum particles is applied to the surface of the aluminum alloy composite foil.

[0085] The modified composite material is made of the following raw materials in percentage: 0.32% of silicon dioxide, 8% of Zn-Al alloy powder, 23% of PU / EP polymer, 26% of D-230 curing agent, 23% of silane coupling agent KH-550, 5% of OP-10 emulsifier, 2% of 1,4-propylene glycol, 8% of ethyl acetate / xylene, and the balance is distilled water.

[0086] Nano-SiO2 undergoes a hydrolysis reaction under a specific environment and eventually turns into a gel, and then the solvent is evaporated by heating or other methods to become an oxide gel with a grid structure, wherein the precursor is a metal salt or an alkoxide metal;

[0087] Among them, the hydroxyl group replaces the alkoxy group (-OC2H5) in ethyl orthosilicate to obtain the product silicic acid; then the various silicic acid monomers undergo dehydration reaction and condensation reaction to obtain nano-SiO2.

[0088] The preparation process of the modified composite material is as follows:

[0089] S1. Mix polyurethane and epoxy resin in a ratio of 1:32 and stir at high speed for 1 hour. Sampling and testing until the free isocyanate group (-NCO) content in the sample is less than 0.1%. Then, a uniform mixture of propylene glycol butyl ether and silane coupling agent KH-550 in a ratio of 1:12 and stirred for 15 minutes is slowly added to the mixed resin of polyurethane / epoxy resin and stirred at high speed for 1 hour. The raw materials of polyurethane and epoxy resin need to be dehydrated before use. Dehydration treatment: put the raw materials into a vacuum drying oven, evacuate, heat at 110°C for 2 hours, cool to 50°C after drying and keep warm for use;

[0090] The mixture of propylene glycol butyl ether and silane coupling agent KH-550 is added to the mixed resin of polyurethane / epoxy resin by step-by-step mixing, and the propylene glycol butyl ether and silane coupling agent KH-550 are evenly divided into 10 parts;

[0091] Preliminary mixing: Take 6 parts of propylene glycol butyl ether and silane coupling agent KH-550, mix them, stir at a stirring speed of 12r / min, and stir for 7min;

[0092] Constant temperature: slowly add the mixture of propylene glycol butyl ether and silane coupling agent KH-550 into the mixed resin of polyurethane / epoxy resin, control the temperature within 35°C, and stir slowly;

[0093] Heating: raising the temperature to 45°C and maintaining it for 32 minutes, and in the maintaining stage, adding propylene glycol butyl ether to the mixed resin in the form of drops, and each time 10 drops are added, standing for 10 minutes, until all the propylene glycol butyl ether is added; similarly, the silane coupling agent KH-550 is added to the mixed resin by this method, and during the dropwise addition and mixing, the temperature of propylene glycol butyl ether and silane coupling agent KH-550 when dropping is consistent with the temperature after heating, the aluminum alloy in the alloy powder is spherical aluminum, and the spherical aluminum is dispersed in anhydrous ethanol, and then triethanolamine is added, and the hydroxylated spherical aluminum is obtained by heating, stirring, washing, and drying;

[0094] The weight ratio of spherical aluminum powder, anhydrous ethanol and triethanolamine is 74:31:2, and the diameter of the spherical aluminum is 7 μm;

[0095] S2, adding nano-SiO2 to the mixed solution obtained in step S1, stirring at high speed for 30 minutes, slowly adding weighed Zn-Al alloy powder, and then adding emulsifier OP-10 and defoamer and stirring at high speed until the slurry is completely dispersed, to obtain a mixed base liquid A;

[0096] S3, take appropriate amount of curing agent polyetheramine D-230 and accelerator DMP-30 and stir them thoroughly, then weigh ethyl acetate / xylene solvent in a certain proportion to the resin and mix them and continue stirring to obtain mixed base liquid B;

[0097] S4. Mix the above-mentioned mixed base liquids A and B, and stir them at high speed using a magnetic stirrer for 3 hours to obtain a modified composite coating.

[0098] In the comparative example, the modified aluminum alloy composite foil was prepared without adding the modified composite material.

[0099] Examples 1-3, by changing the mass ratio of the alloy powder, the modified composite material, and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane, Example 1 (7:1:1), Example 2 (7:2:1), Example 3 (7:3:1).

[0100] In order to prove the performance effect of the modified aluminum alloy composite foil prepared in the embodiment, the following verification experiments are provided:

[0101] Corrosion resistance test: The corrosion resistance test was carried out according to the requirements of "Water-based Aluminum Slurry HG / T2456.5-2016", and certain adjustments were made, as follows: 1g of the aluminum pigment of the embodiment, comparative example and reference example was added to tap water, a 1mol / L hydrochloric acid aqueous solution and a 1mol / L sodium hydroxide solution, respectively, and heated at 100°C for 12h, and the hydrogen production was tested to determine the corrosion resistance of the aluminum pigment. The test results are shown in Table 1.

[0102] Table 1 Performance verification experimental results

[0103]

[0104] Data Analysis:

[0105] It can be seen from Examples 1-3 that the modified aluminum alloy composite foil prepared by the present invention has the ability to cope with harsh environments such as high temperature, acid, and alkali, and can ensure that even if exposed to outdoor environments for a long time, it can maintain good performance and meet the use requirements of coatings in the air-conditioning industry. In addition, compared with traditional graphene composite aluminum foil, the modified aluminum alloy composite foil prepared by the present invention has a higher effect in corrosion resistance.

[0106] From the comparison between Examples 1-3 and the comparative example, it can be seen that the modified composite material improves the corrosion resistance of the modified aluminum alloy composite foil, so that it can effectively cope with harsh environments such as high temperature, acid and alkali. This is mainly due to the bonding effect of nano-SiO2 and a small amount of free isocyanate groups (-NCO) in the polyurethane and epoxy resin, thereby improving the protection ability of flaky aluminum. Under the premise of the thickness of the bottom wrapping, it has higher corrosion resistance, and the low thickness of the wrapping maintains the gloss of the flaky aluminum. At the same time, 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane can improve the dispersibility and compatibility in the modified aluminum alloy composite foil.

[0107] SiO2 is widely present in nature. Since SiO2 is the most stable compound of silicon and has the characteristics of high melting point and high hardness, it is widely used in plastics, rubber, anti-corrosion coatings, printing, military materials and other fields. Nano SiO2 is a white powder with fluffy shape, tasteless, non-toxic and high temperature resistant inorganic non-metallic material. The most important feature is that the particle size is very small, about 20 to 200nm. It has many good properties, large specific surface area, fine chemical purity, and strong adsorption capacity. There are a large number of unsaturated residual bonds and hydroxyl groups in different bonding states on the surface of nano SiO2. The molecular structure is a three-dimensional chain structure, which can bond with epoxy resin and its polymer resin to improve the mechanical properties and anti-corrosion properties of the coating. In the field of heavy anti-corrosion coatings, adding SiO2 not only has excellent performance but also reduces the production cost of coatings.

[0108] Electrochemical impedance spectroscopy (EIS) is used to analyze diffusion and kinetics in electrochemical reactions and is the main method for studying electrode materials, conductive molecules, and corrosion protection mechanisms. By analyzing the electrochemical impedance of nanocomposite coatings at different immersion times, the corrosion process of SiO2 nanocomposite coatings is divided into different corrosion stages. The corrosion of the coatings and coatings / substrates at each corrosion stage after being immersed in 3.5% NaCl solution for different times is analyzed.

[0109] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.

Claims

1. A modified aluminum alloy composite foil, characterized in that: The composite foil is prepared by compounding alloy powder and modified composite material; The alloy powder is made of the following percentage raw materials: 17-29% zinc, 0.02-0.07% lanthanum, 0-0.05% copper, 0.02-0.09% iron, and the balance is aluminum; The modified composite material is made of the following raw materials in percentage: 0.22-0.35% of silicon dioxide, 8-9% of Zn-Al alloy powder, 22-28% of PU / EP polymer, 26-30% of D-230 curing agent, 23-25% of silane coupling agent KH-550, 5-7% of OP-10 emulsifier, 2-3% of 1,4-propylene glycol, 8-10% of ethyl acetate / xylene, and the balance is distilled water; The preparation process of the modified composite material is as follows: S1. Mix polyurethane and epoxy resin in a ratio of 1:32-38 and stir at high speed for 1 hour. Sampling and testing until the free isocyanate group (-NCO) content in the sample is less than 0.1%. Then, slowly add the uniform mixture of propylene glycol butyl ether and silane coupling agent KH-550 in a ratio of 1:11-13 and stir for 15 minutes into the mixed resin of polyurethane / epoxy resin and stir at high speed for 1 hour. S2, adding nano-SiO2 to the mixed solution obtained in step S1, stirring at high speed for 30 minutes, slowly adding weighed Zn-Al alloy powder, and then adding emulsifier OP-10 and defoamer and stirring at high speed until the slurry is completely dispersed and uniform, to obtain a mixed base liquid A; S3, take appropriate amount of curing agent polyetheramine D-230 and accelerator DMP-30 and stir them thoroughly, then weigh ethyl acetate / xylene solvent in a certain proportion to the resin and mix them and continue stirring to obtain mixed base liquid B; S4. Mix the above-mentioned mixed base liquids A and B, and stir them at high speed using a magnetic stirrer for 3 hours to obtain a modified composite coating.

2. A modified aluminum alloy composite foil according to claim 1, characterized in that: In step S1, the raw materials of polyurethane and epoxy resin need to be dehydrated before use; Dehydration treatment: Place the raw materials in a vacuum drying oven, evacuate the air, heat at 110-120℃ for 2-3h, and after drying, cool to 50℃ and keep warm for later use.

3. The modified aluminum alloy composite foil according to claim 1, characterized in that: In the step S1, a mixture of propylene glycol butyl ether and silane coupling agent KH-550 is added to the mixed resin of polyurethane / epoxy resin by step-by-step mixing, and propylene glycol butyl ether and silane coupling agent KH-550 are evenly divided into 10 parts; Preliminary mixing: Take 6 parts of propylene glycol butyl ether and silane coupling agent KH-550, mix them, stir at a stirring speed of 12-15r / min, and stir for 6-8min; Constant temperature: slowly add the mixture of propylene glycol butyl ether and silane coupling agent KH-550 into the mixed resin of polyurethane / epoxy resin, control the temperature within 35-38℃, and stir slowly; Heating: Raise the temperature to 45°C and maintain for 30-35 minutes. During the maintenance period, add propylene glycol butyl ether to the mixed resin in the form of drops, and add 10-12 drops each time, and let it stand for 10 minutes until all the propylene glycol butyl ether is added. Similarly, use this method to add the silane coupling agent KH-550 to the mixed resin.

4. The modified aluminum alloy composite foil according to claim 1, characterized in that: During the dropwise addition and mixing, the temperature of propylene glycol butyl ether and silane coupling agent KH-550 during the dropwise addition is consistent with the temperature after the temperature increase.

5. The modified aluminum alloy composite foil according to claim 1, characterized in that: The aluminum alloy in the alloy powder is spherical aluminum, and the spherical aluminum is dispersed in anhydrous ethanol, and then triethanolamine is added, and the mixture is heated, stirred, washed, and dried to obtain hydroxylated spherical aluminum; Wherein, the weight ratio of spherical aluminum powder, anhydrous ethanol and triethanolamine is 62-80:21-35:1-2.

6. A modified aluminum alloy composite foil as claimed in claim 5, characterized in that: The diameter of the spherical aluminum is 6-8 μm.

7. The modified aluminum alloy composite foil according to claim 1, characterized in that: Nano-SiO2 undergoes hydrolysis reaction under specific conditions and eventually turns into gel, and then the solvent evaporates through heating or other methods to become an oxide gel with a grid structure, in which the precursor is a metal salt or alkoxide metal; Among them, the hydroxyl group replaces the alkoxy group (-OC2H5) in ethyl orthosilicate to obtain the product silicic acid; then dehydration reaction and condensation reaction occur between the various silicic acid monomers to obtain nano-SiO2.

8. The modified aluminum alloy composite foil according to claim 1, characterized in that: When preparing the alloy powder, metal iron, lanthanum, copper and aluminum are melted and mixed to obtain a commingled alloy, the commingled alloy is homogenized at a temperature of 560-580° C. for 8 hours to obtain a composite alloy, and the composite alloy is ball-milled to obtain the alloy powder.

9. A process for preparing a modified aluminum alloy composite foil, using the aluminum alloy composite foil according to any one of claims 1 to 7, characterized in that: The steps include: The alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane are mixed, and the slurry is coated and dried to obtain an aluminum alloy composite foil; The mass ratio of the alloy powder, the modified composite material and 2-[methoxy(polyoxyethylene)propyl]trimethoxysilane is 7:1-3:

1.

10. The process for preparing a modified aluminum alloy composite foil according to claim 9, characterized in that: After the aluminum alloy composite foil solidifies, an electromagnetic heating roller is used to roll the surface of the aluminum alloy composite foil at a pressure of 2.1-2.5MPa and a heating temperature of 660-670°C; the rolling is repeated 2-3 times; Each time the rolling process is performed, a layer of spherical aluminum particles is applied to the surface of the aluminum alloy composite foil.

Citation Information

Patent Citations

  • A graphene composite aluminum foil

    CN116904104B